(untitled) (Eurasian Journal of Ecology, 2016)
Different environmental factors such as temperature, pH, and concentration of mineral salts, ultraviolet on the activity of biosurfactants were studied. This surface-active substances were produced by strains of hydrocarbon – oxidizing microorganisms Dietzia maris MB3. The toxicity of selected biosurfactants was studied on the following crops: wheat “AKM-Niva”, peas “Substar” and radish “Ascanius”.